2021
DOI: 10.3390/agriculture11090879
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Stored Products’ Pests with Plant Secondary Metabolites: A Review

Abstract: To date, only a handful of pesticides have been authorized by the European Council for the protection of stored grains. Resistance issues and ecotoxicity concerns necessitate the development of ecofriendly tools in that direction. In this review, we refer to the recent findings on plant extracts and pure plant-derived substances with promising biological activity and the potential to be used as biopesticides for stored products. The main aim of biopesticides is to be effective against target pests, without har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 185 publications
(186 reference statements)
0
9
0
2
Order By: Relevance
“…Nuclear magnetic resonance: 1 H and 13 C NMR spectra were recorded by a Bruker AC-300 spectrometer (Bruker, Billerica, MA) at 300 and 75 MHz, respectively, using CDCl 3 as the solvent. 1 H NMR data was reported as position (δ), relative integral, multiplicity, and the assignment of the atom, while 13 C NMR data was reported as position (δ) and assignment of the atom. 20 Infrared spectroscopy: IR spectra were recorded with Nicolet iS 50-Fourier-transform IR spectrometers (Thermo Fisher Scientific, USA).…”
Section: T H Imentioning
confidence: 99%
“…Nuclear magnetic resonance: 1 H and 13 C NMR spectra were recorded by a Bruker AC-300 spectrometer (Bruker, Billerica, MA) at 300 and 75 MHz, respectively, using CDCl 3 as the solvent. 1 H NMR data was reported as position (δ), relative integral, multiplicity, and the assignment of the atom, while 13 C NMR data was reported as position (δ) and assignment of the atom. 20 Infrared spectroscopy: IR spectra were recorded with Nicolet iS 50-Fourier-transform IR spectrometers (Thermo Fisher Scientific, USA).…”
Section: T H Imentioning
confidence: 99%
“…Their use is offered in many areas of pest control. Edible and essential oils have been tested as botanical insecticides against a wide range of pests that attack both stored commodities and standing crops [ 128 , 129 ]. From an ecological and partly toxicological point of view, plant oils are valued because they are biodegradable and thus do not tend to accumulate in the environmental chains.…”
Section: Gel Formulations With Natural Plant Extracts As Pesticides A...mentioning
confidence: 99%
“…Most of these extracts were either attractants or had no effect [40]. Nikolaou (2021) tested the essential oil of Clausena anisata, and observed that it was highly toxic to the larval stages, and prevented the emergence of adults. When Mentha piperita and Salvia officinalis were added to a polylactic acid solution, P. interpunctella experienced considerable contact toxicity, with M. piperita exhibiting more toxicity than S. officinalis [41].…”
Section: Biochemical Controlmentioning
confidence: 99%